CANNABIDIOL AS A NOVEL THERAPY FOR ALZHEIMER’S DISEASE - Raquel Xavier Viana, Tereza (2023)
Alzheimer’s disease (AD) is a progressive and incurable neurodegenerative condition that affects millions of people worldwide. The search for effective treatments for this disease has long been a priority in healthcare. In recent years, interest in the use of cannabidiol (CBD), one of the compounds found in the Cannabis sativa plant, has grown due to its potential therapeutic properties. A literature review was conducted covering searches in electronic databases, such as PubMed, SciELO and LILACS, with the aim of gathering as much information on the selected theme. Descriptors such as “Alzheimer”, “Cannabidiol”, “Treatment” and “CBD” were used, combined with the Boolean operator AND. The selection of articles considered the date of recent publication, limited to the last 10 years, as well as research related to the same theme and articles in Portuguese or foreign language (English). Duplicate articles, those that did not fit the proposed theme, as well as theses, monographs and dissertations were excluded. It was observed that CBD has characteristics often associated with Alzheimer’s therapy, such as anti-inflammatory, neuroprotective properties and mild adverse effects. The results indicated that the use of CBD in Alzheimer’s treatment shows promising potential. CBD was found to be especially beneficial for patients with neurodegenerative diseases. In conclusion, Cannabis is a viable substance given its promising therapeutic properties in the context of neuronal health, and its approach shows positive results in terms of recovery, symptomatologic improvement, and quality of life for patients affected by Alzheimer’s. Despite limitations and the need for further studies, results to date suggest that CBD may represent a promising option for symptomatic treatment and possibly even for modifying disease progression. However, it is critical to conduct larger-scale controlled clinical trials to confirm these findings and establish clear guidelines for its clinical use. These results may provide input for the development of future research and promising therapeutic strategies for Alzheimer’s disease.